Plio-Pleistocene slope construction off western Nova Scotia, Canada. - Swift, S.A.; Uchupi, E. (Cuadernos de Geología Ibérica, 1991)
Atlantic continental síopes have an average gradient of 70 and tend to be irregularly incised by submarino canyons witb re]iefs of about 1000 m. In contrast the slope off western Nova Seotia (from 61 030'W to 650W), Canada, is smooth (relief <300 m) and has declivities ranging from 2.60 off Emerald Bank to 1 .60 off LaHave Bank. This lack of deep relief is dueto a combination of low subsidence and sedimentation ratos during Late Cretaceous and Cenozoic. As a result of this low gradient, canyons that formed on the siope during periods of íow sea level and high sodiment supply rarely survived, being filied during subsequent regressions when sedimeul supply was Iess. High sedimentation rates by subglacial sedirnent plumes during lato Wisconsin did lead, howover, to extensive sediment failure that produced Jow relief slump and debris flow structures.